Neurokinin A monitoring of response to interferon alpha in a patient with an advanced small bowel neuroendocrine tumour uncontrolled by somatostatin analogue therapy. (March 2017) - Ardill, Joy ES; Johnston, Brian T; McCance, David R; Eatock, Martin
A 52-year-old lady presented with a history of occasional, severe abdominal cramps, postprandial diarrhoea and weight loss. After routine gastrointestinal investigations, she was diagnosed with irritable bowel syndrome. Over six months, she developed occasional facial flushing prompting assessment of neuroendocrine tumour markers. Urinary 5HIAA, 5HT, chromogranin A and neurokinin A were significantly elevated. Scans showed extensive hepatic metastases but did not show the location of a primary tumour. Somatostatin analogue therapy was commenced but despite increasing doses, symptoms increased and biomarkers rose dramatically. Interferon alpha was introduced concomitant with somatostatin analogue therapy. Biomarkers were monitored regularly. Within six months, symptoms abated and biomarkers reduced, continuing to fall over the next year, close to reference range. To manage side-effects of interferon alpha, dose was reduced from time to time. During these short periods, neurokinin A showed significant transient increases (75–150 ng/L) and carcinoid symptoms returned. For more than seven years, and with the co-operation of the patient, a balance was achieved between interferon alpha side-effects and disease control. Scans showed tumour load to be stable. The patient survived for 10 years post diagnosis. She chose to discontinue interferon alpha and received peptide receptor radiation therapy in her final year. Throughout, neurokinin A remained the most sensitive monitor of her disease progression.